Evaluation Of Tertiary Levels Irrigation Performance Metro City Technical Unit Of Irrigation Sekampung Batanghari Irrigation Areas - Nur Zun Viqhy; R.A Bustomi Rosadi; Nugroho Haryono; oktafri - (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2012)
This study aimed to determine the effectiveness of performance irrigation at tertiary level in technical unit irrigation Metro city of Sekampung Batanghari irrigation areas.  The study was conducted at tertiary level irrigation in sekampung Batanghari irrigation areas on KBH 5 Ki 2 (upstream), KBH 6 Ki (middle), and KBH 7A Ki (downstream). The instrument that used in this research were current meter, stopwatch, Sekampung Batanghari irrigation areas map, and secondary of data.  The study was conducted using secondary data collection methods and measurement directly on the field.  The result showed that (1) the performance of irrigation in UPT Metro city irrigation were less effective that  showed from the value of the irrigation complexity is quite simple, (2) the efficiency of water delivery at tertiary level irrigation in metro city that classified as unoptimal, there is 81,23 % and still under the preliminary draft, (3) the overall irrigation performance in the tertiary level of UPT Metro city still low. Keywords: effectiveness of performance, irrigation, Metro city, Sekampung Batanghari